Women leaders in Cardiology. Contemporary profile of the WHO European region. Issue 1 (15th July 2021) - Borrelli, Nunzia; Brida, Margarita; Cader, Aaysha; Sabatino, Jolanda; Czerwińska-Jelonkiewicz, Katarzyna; Shchendrygina, Anastasia; Wood, Alice; Allouche, Emna; Avesani, Martina; Gok, Gulay; Marchenko, Oksana; Calvieri, Camilla; et al.
Abstract: Aims: Women's participation is steadily growing in medical schools, but they are still not sufficiently represented in cardiology, particularly in cardiology leadership positions. We present the contemporary distribution of women leaders in cardiology departments in the World Health Organization European region. Methods and results: Between August and December 2020, we applied purposive sampling to collect data and analyse gender distribution of heads of cardiology department in university/third level hospitals in 23 countries: Austria, Azerbaijan, Belgium, Bosnia-Herzegovina, Croatia, France, Germany, Greece, Italy, North Macedonia, Morocco, Poland, Portugal, Russia, Serbia, Slovakia, Slovenia, Spain, Switzerland, Tunisia, Turkey, Ukraine, and the UK. Age, cardiology subspecialty, and number of scientific publications were recorded for a subgroup of cardiology leaders for whom data were available. A total of 849 cardiology departments were analysed. Women leaders were only 30% (254/849) and were younger than their men counterpart (♀ 52.2 ± 7.7 years old vs. ♂ 58.1 ± 7.6 years old, P = 0.00001). Most women leaders were non-interventional experts (♀ 82% vs. ♂ 46%, P < 0.00001) and had significantly fewer scientific publications than men ♀ 16 [interquartile range (IQR) 2–41] publications vs. ♂ 44 (IQR 9–175) publications, P < 0.00001. Conclusion: Across the World Health Organization European region, there is a significant gender disparity in cardiology leadership positions. Fostering a diverse and inclusive workplace is a priority to achieve the full potential and leverage the full talents of both women and men. Graphical Abstract: